Foam rolling reduced total creatine kinase in acute muscle inflammation following long-distance running - Mohammad Arif Ali; Bayu Pangestu; Setya Rahayu; Gustiana Mega Anggita; Dewi Marfu’ah Kurniawati; Etika Ratna Noer; Ani Mazlina Dewi Mohamed (Journal Sport Area, 2023)
Strenuous physical activity is able to cost muscle damage. In urban society, ten kilometers running has become a modern culture. It induces acute inflammation as a normal physiological response. Conversely, a foam roller is known as a self-myofascial release (SMR) technique which can be done individually. Previous studies stated that foam rolling (FR) could increase flexibility, and reduce muscle pain sensation. However, there is still a limited supply of scientific evidence to prove its positive effects, especially through biomarkers such as creatine kinase (CK). This study aims to elucidate the beneficial effects of a foam roller in CK concentration after 10 kilometers of running which induces DOMS. A quasi-repeated measures design was elected as an approach to conducting this study. The purposive sampling technique was used to obtain the subjects (n= 10). Creatine kinase measurements were performed before 10 km running and 3 days post running by using the COBAS INTEGRA 400 Plus Test (the UV-test concept). Repeated Measures ANOVA was used to determine the effect of FR on CK. Ten kilometers of running increased Total CK concentration, pre-test data was 146.2 ± 36.3 (U/L), and 24 hours was 452.3 ± 216.5 (U/L). Creatine Kinase decreased at 48 hours (300.6 ± 117.6 (U/L), and 72 hours (238.4 ± 67.5 (U/L) post-application of foam rolling. We conclude that long distance running increased significantly total CK, and foam rolling might decrease CK concentration in the blood.